A shielding harmful light, flame-retardant, antibacterial multifunctional composite film and a preparation method thereof
Patent Information
- Application Number
- CN202611093182.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-09-25
AI Technical Summary
前者常因纳米粒子表面能过高导致的严重团聚,引发光散射损耗,导致薄膜透明度锐减并削弱力学性能;后者则面临潜在的生物毒性与迁移泄漏带来的环境持久性风险
[0033](1)本发明提供了一种方法简单且易于规模化生产的制备兼具优异光屏蔽性、阻燃安全性、抗菌活性及高机械强度的多功能复合薄膜。
Smart Images

Figure CN122810448A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of bio-based functional materials technology. Specifically, this invention relates to a method for preparing a multifunctional composite film with high mechanical strength, which is constructed by introducing the natural chromophore molecule gardenia yellow and the functionalized macromolecule phosphorylated chitosan onto a carboxymethylated cellulose hydrogel substrate. Background Technology
[0002] In response to the severe environmental crisis caused by traditional petroleum-based packaging materials, developing high-value-added, multifunctional packaging and protective films using sustainable natural biomolecules has become a key trend in the field of green materials. Cellulose, as a bio-based polymer with excellent film-forming potential, shows great promise in flexible optoelectronic devices, food packaging, and the protection of photosensitive items. However, due to inherent chemical structure limitations, pure cellulose films severely lack UV / high-energy blue light protection and fire safety, and also lack activity against external microbial contamination, which greatly restricts its expansion into high-value-added fields.
[0003] To overcome these limitations, endowing cellulose films with multifunctional properties has become a research focus in recent years. However, existing strategies often fall into a trade-off between performance gains and interfacial compatibility and environmental friendliness. For example, in the dimension of optical protection, traditional methods often rely on doping inorganic semiconductor nanoparticles (such as TiO2 and ZnO) or synthesizing organic ultraviolet absorbers (such as benzotriazoles). The former often leads to severe aggregation due to excessively high nanoparticle surface energy, causing light scattering loss, resulting in a sharp decrease in film transparency and weakened mechanical properties; the latter faces potential risks of biotoxicity and environmental persistence due to migration and leakage.
[0004] The flammability of cellulose membrane materials also poses a significant hazard in safety-sensitive fields. Traditional flame retardants (such as halogenated and phosphorus-based retardants) often sacrifice the mechanical properties of the material while improving safety, and the harmful fumes released during combustion can easily cause secondary pollution. Summary of the Invention
[0005] The present invention aims to at least partially solve one of the technical problems in the related art. To this end, embodiments of the present invention provide a multifunctional composite film that shields harmful light, is flame-retardant, and antibacterial, as well as its preparation method and application.
[0006] Firstly,
[0007] This invention provides a method for preparing a multifunctional composite film (GPCS-CCFs) that shields harmful light, is flame-retardant, and antibacterial, comprising the following steps:
[0008] S1. Dissolve carboxymethyl cellulose powder in an aqueous solution of lithium hydroxide-urea, disperse it thoroughly, freeze it, thaw it at room temperature, place it in a mold, add ethanol to solidify it, and obtain a transparent cellulose hydrogel.
[0009] S2. Gardenia yellow (GY) and phosphorylated chitosan (PCS) were added to deionized water and dispersed at high speed to obtain a composite solution.
[0010] S3. After cutting the cellulose hydrogel obtained in step S1 into pieces, immerse it completely in the composite solution obtained in step S2 and soak it thoroughly so that the functional components can fully penetrate into the three-dimensional network of the hydrogel.
[0011] S4. The soaked film is dried to prepare the composite film.
[0012] In this embodiment of the invention, gardenia yellow and phosphorylated chitosan were selected as functional components to prepare a multifunctional composite film that shields harmful light, is flame retardant, and antibacterial. While possessing multiple functions, it can also maintain high transparency and mechanical properties.
[0013] In some embodiments of the preparation method, in step S1, the carboxymethyl cellulose powder is obtained by adding cellulose powder to an aqueous solution containing sodium chloroacetate and sodium hydroxide to carry out a carboxymethylation reaction. After the reaction is completed, the powder is washed with deionized water until neutral, dried, and ground to obtain carboxymethyl cellulose powder.
[0014] In some embodiments of the preparation method, the cellulose powder is one or more of cotton pulp cellulose powder, wood pulp cellulose powder, or straw cellulose powder; the mass concentration of sodium hydroxide is 10%–20%; the concentration of sodium chloroacetate is 0.5–1.5 M; the solid-liquid ratio of the cellulose powder to the aqueous solution containing sodium chloroacetate and sodium hydroxide is 1:30–1:40 g / mL; the carboxymethylation reaction temperature is 50℃–70℃; and the reaction time is 2 h–5 h.
[0015] In some embodiments of the preparation method, in step S1, the mass fraction of lithium hydroxide in the lithium hydroxide-urea aqueous solution is 5% to 10%, the mass fraction of urea is 10% to 20%, the freezing temperature is -50℃ to -10℃, the freezing time is 2 h to 12 h, the curing temperature is 10℃ to 25℃, and the curing time is 4 h to 12 h.
[0016] In some preferred embodiments, the lithium hydroxide-urea aqueous solution contains 8% lithium hydroxide by mass and 15% urea by mass.
[0017] In some embodiments of the preparation method, in step S2, the mass ratio of gardenia yellow, phosphorylated chitosan, and deionized water in the composite solution is 0.4–1.0 g: 1–2 g: 100 g; preferably 0.6–0.8 g: 1.2–1.8 g: 100 g; more preferably 0.8 g: 1.5 g: 100 g.
[0018] In some embodiments of the preparation method, the phosphorylated chitosan is prepared by adding chitosan to an aqueous solution of acetic acid and phosphoric acid, stirring and reacting at 40-60°C for 3-5 hours, then pouring it into anhydrous ethanol to precipitate a white precipitate, and washing, drying and pulverizing with ethanol to obtain phosphorylated chitosan powder.
[0019] In some embodiments of the preparation method, the volume concentration of acetic acid in the aqueous solution of acetic acid and phosphoric acid is 4-8%, and the volume concentration of phosphoric acid is 35-40%.
[0020] In some examples of the preparation methods, the ratio of chitosan to phosphoric acid is 1 g: (9-12) mL.
[0021] In some embodiments of the preparation method, in step S2, the high-speed dispersion is carried out at a rotation speed of 8000–12000 r / min for 10–20 min.
[0022] In some embodiments of the preparation method, step S3 is carried out at room temperature and in the dark, and the soaking time is 2 to 4 hours.
[0023] Secondly,
[0024] This invention provides a multifunctional composite film that shields harmful light, is flame-retardant, and antibacterial, and is prepared by the above-described preparation method.
[0025] In some embodiments, the composite film has a thickness of 0.10~0.15mm; a shielding efficiency of ≥52.5% at 320~400 nm (UV-A), a shielding efficiency of ≥55.6% at 280~320 nm (UV-B), a shielding efficiency of ≥72.5% at 400~450 nm (high-energy harmful blue light, HEBL), a limiting oxygen index of ≥30%, an antibacterial rate of ≥70% against Escherichia coli, an antibacterial rate of ≥70% against Staphylococcus aureus, and a tensile strength of ≥80 MPa.
[0026] In some preferred embodiments, the composite film has a thickness of 0.10~0.15mm; a shielding efficiency of ≥60.0% at 320~400 nm (UV-A), ≥60.0% at 280~320 nm (UV-B), ≥85.0% at 400~450 nm (high-energy harmful blue light, HEBL), a limiting oxygen index of ≥31%, an antibacterial rate of ≥70% against Escherichia coli, an antibacterial rate of ≥70% against Staphylococcus aureus, and a tensile strength of ≥80 MPa.
[0027] In some more preferred embodiments, the composite film has a thickness of 0.10~0.15mm; a shielding efficiency of ≥65.0% at 320~400 nm (UV-A), ≥65.0% at 280~320 nm (UV-B), ≥90.0% at 400~450 nm (high-energy harmful blue light, HEBL), a limiting oxygen index of ≥31%, an antibacterial rate of ≥80% against Escherichia coli, an antibacterial rate of ≥75% against Staphylococcus aureus, and a tensile strength of ≥80 MPa.
[0028] Furthermore, the composite film maintains a high transmittance of over 90% and a low haze of 1.8~2.0% at a wavelength of 600 nm.
[0029] Thirdly,
[0030] The present invention also provides the application of the above-mentioned composite film in the fields of flexible optoelectronic devices and packaging materials.
[0031] In some embodiments, the composite film is used to prepare screen protectors for electronic devices (such as mobile phone screen protectors, computer screen protectors, etc.) or as a protective liner for photosensitive foods.
[0032] The present invention has the following advantages and beneficial effects:
[0033] (1) The present invention provides a method for preparing a multifunctional composite film with excellent light shielding, flame retardant safety, antibacterial activity and high mechanical strength, which is simple and easy to scale up.
[0034] (2) The composite film prepared by the present invention has excellent full-band harmful light precise shielding performance, and has successfully achieved a shielding rate of ≥52.5% in 320~400 nm, a shielding rate of ≥55.6% in 280~320 nm, and a shielding rate of ≥72.5% for high-energy harmful blue light.
[0035] (3) This invention improves the flame retardant properties of the film by introducing phosphorylated chitosan into the film, through the synergistic effect of P catalytic char formation in the condensed phase and N diluting combustible gases in the gas phase. This significantly increases the limiting oxygen index of the material to over 31.1%, giving the bio-based cellulose material an excellent fire safety barrier.
[0036] (4) In this invention, the carboxyl and hydroxyl groups of gardenia yellow react with the amino and phosphate groups of phosphorylated chitosan in aqueous solution through electrostatic and hydrogen bonding to form a precomplex. This precomplex further reacts with the carboxyl and hydroxyl groups on the cellulose chain through electrostatic and hydrogen bonding to form a stable three-dimensional network structure. This not only ensures the stable performance of the film's anti-blue light and anti-UV properties, but also significantly improves the film's antibacterial and mechanical properties.
[0037] (5) The present invention uses the hydrogel immersion method, which realizes the homogeneous interpenetration of multiple components through the strong hydrogen bonding and electrostatic interaction between macromolecular chains, effectively avoiding the phase separation and component aggregation defects caused by the traditional blending method. The prepared composite film has excellent mechanical tensile strength and toughness, making it less prone to cracking or damage during use. Attached Figure Description
[0038] Figure 1 Characterization images of CS, PCS, GY, CCF, and GPCS-CCFs are shown below. (a) Preparation process of PCS. (b) FTIR of CS and PCS. (c) FTIR of virgin cellulose fibers and carboxymethylated cellulose fibers. (d) FTIR of GY, CCF, and GPCS-CCFs. (e) XRD of GY, CCF, and GPCS-CCFs. (f) XPS of CCF and GPCS-CCF3. (g) XPS of P2p in GPCS-CCF3. (h) SEM of CCF and GPCS-CCFs.
[0039] Figure 2 The diagram shows the UV and blue light shielding performance of GPCS-CCFs, where (a) is a photograph of CCF and GPCS-CCFs; (b) is the transmittance of CCF and GPCS-CCFs; (c and d) are the transmittances of CCF and GPCS-CCFs at different wavelengths; (e) is the shielding efficiency of CCF and GPCS-CCFs at different wavelengths; and (f) is the UV shielding performance test results of CCF and GPCS-CCFs.
[0040] Figure 3 This is a comparison chart of haze levels between CCF and GPCS-CCFs.
[0041] Figure 4The results of thermal stability and limiting oxygen index (LOI) of CCF and GPCS-CCFs are shown in the figure. (a) is the TGA curve of CCF and GPCS-CCFs, (b) is the DTG curve of CCF and GPCS-CCFs, and (c) is the limiting oxygen index (LOI) of CCF and GPCS-CCFs.
[0042] Figure 5 Images of CCF and GPCS-CCFs and their water contact angles (WCA) are shown, where (a) is the image and (b) is the water contact angle.
[0043] Figure 6 The water vapor permeability and oxygen and carbon dioxide barrier properties of CCF and GPCS-CCFs are given, where (a) is the water vapor permeability and (b) is the oxygen and carbon dioxide barrier properties.
[0044] Figure 7 The antibacterial properties of CCF and GPCS-CCFs are shown, with (a and b) images of Escherichia coli and Staphylococcus aureus co-cultured with CCF and GPCS-CCFs. (c and d) The inhibition rates of CCF and GPCS-CCFs against Escherichia coli and Staphylococcus aureus.
[0045] Figure 8 The figures show the correlation of mechanical properties of CCF and GPCS-CCFs, where (a) are the stress-strain curves of CCF and GPCS-CCFs, (b) are the corresponding tensile strengths of CCF and GPCS-CCFs, and (c) is a photograph showing the flexibility of GPCS-CCF3. Detailed Implementation
[0046] The embodiments of the present invention are described in detail below. These embodiments are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0047] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.
[0048] When a value is described as a range, it should be understood that such disclosure includes disclosure of all possible subranges within that range, as well as the specific numerical value falling within that range, regardless of whether the specific numerical value or specific subrange is explicitly specified.
[0049] In this document, the terms "first aspect," "second aspect," and "third aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0050] In this article, the terms "multiple" or "various" are used unless otherwise specified, referring to a quantity greater than or equal to 2. For example, "one or more" means one or more types.
[0051] In this document, terms such as "preferred," "more preferred," and "better" are used only to describe implementation methods or embodiments with better effects, and should be understood as not constituting a limitation on the scope of protection of this invention.
[0052] Developing functional thin films that can effectively block ultraviolet radiation and high-energy blue light has become a hot research direction in materials science. However, achieving excellent light-blocking performance while simultaneously maintaining satisfactory mechanical strength, high transparency, and environmental friendliness remains a core challenge for large-scale practical applications. Furthermore, the inherent flammability of cellulose-based materials significantly limits their deployment in applications with stringent safety requirements.
[0053] To optimize the optical properties of the thin film, this invention synthesizes carboxymethylated cellulose fibers via an etherification process, effectively improving light transmittance and reducing haze. Subsequently, these carboxymethylated cellulose fibers are dissolved in a lithium hydroxide-urea aqueous solution and cured to obtain a transparent carboxymethylated cellulose hydrogel. Finally, the hydrogel is immersed in a PCS / GY solution to obtain a composite cellulose hydrogel. These hydrogels possess abundant porous structures, effectively adsorbing GY and PCS molecules to construct a composite hydrogel system. The negatively charged carboxymethylated cellulose hydrogel serves as the main structural material. Carboxymethylated cellulose and PCS are bonded by carboxymethyl groups (-CH2COO-). - ) and amino (-NH3) +The electrostatic attraction between PCS and GY molecules is a key factor. The numerous hydroxyl groups on the cellulose backbone can form an extensive hydrogen bond network with the hydroxyl, amino, and phosphate groups on the PCS molecules. The abundant hydroxyl and carboxyl groups on both cellulose and GY molecules can also bind to each other through hydrogen bonding. Furthermore, electrostatic attraction also occurs between PCS and GY molecules. After drying, a high-performance cellulose-based film is finally prepared. During the drying process, the internal structure of the cellulose hydrogel network containing PCS and GY molecules becomes denser, leading to the accumulation of PCS and GY molecules within the cellulose network, thus forming a PCS / GY molecular layer. The formation of this molecular layer enhances the film's UV and blue light shielding properties, as well as its flame retardant properties. Due to these diverse non-covalent intermolecular interactions, the prepared composite film combines high transparency, low haze, flame retardancy, antibacterial properties, and excellent harmful light shielding capabilities. Therefore, as a new generation of environmentally friendly high-end functional film materials, they show great application potential in food packaging, building protection, and optical devices.
[0054] The specific methods for performance testing involved in the embodiments and comparative examples of this invention are as follows:
[0055] (1) Characterization
[0056] Fourier transform infrared (FTIR) spectra were obtained using a Nicolet 6700 Fourier transform infrared spectrometer manufactured by Nicolet Corporation, USA, with 32 scans and a resolution of 4 cm⁻¹. -1 Wavelength range 500-4000 cm -1 X-ray diffraction (XRD) analysis was performed using a Rigaku D / MAX2200VPC diffractometer (Japan), with an X-ray diffraction angle range of 5-60°. X-ray photoelectron spectroscopy (XPS) was performed on the samples using an ESCALAB 250Xi. The microstructure of the samples was characterized using a Hitachi S4800 scanning electron microscope (SEM) (Japan). Thermal mass analysis (TGA and DTG) results were obtained using a Netzsch STA 449 F3 Jupiter instrument (Germany).
[0057] (2) Light transmittance and light shielding rate:
[0058] Transmittance was measured using a UV-Vis spectrophotometer (TU-1950, China).
[0059] The photoprotective properties of the thin film against ultraviolet and blue light were systematically characterized using ultraviolet-visible spectrophotometry. The shielding efficiency for each wavelength band was calculated using the following formula:
[0060]
[0061]
[0062]
[0063] (3) Haze
[0064] According to GB / T 25273-2025 standard, the sample was cut into 50×50 mm pieces and equilibrated at 23±2℃ and relative humidity for 2 hours to ensure a clean and flat surface. An integrating sphere haze meter with a standard C light source was used for testing. After the instrument was fully preheated and stabilized, the sample was clamped and measured. Each sample was tested three times, and the average value was taken as the final haze result for that sample.
[0065] (4) Limiting oxygen index
[0066] The limiting oxygen index of the thin film samples was characterized using an FTT0077 oxygen index tester, in accordance with the requirements of the ASTM D2863 standard test method. The sample size was 80 mm × 10 mm.
[0067] (5) Water contact angle
[0068] Water contact angle testing was conducted at room temperature using a JY-82B video contact angle tester. Distilled water was added to the sample surface by manually rotating a syringe, and droplet images were collected simultaneously. The droplet contact angles on different sample surfaces were measured and analyzed.
[0069] (6) Antibacterial rate
[0070] The antibacterial activity of the membrane against *Escherichia coli* and *Staphylococcus aureus* was evaluated using a colony counting method. Solid culture medium (a distilled aqueous solution containing 0.5% yeast extract, 1% peptone, 1% NaCl, and 2% nutrient agar) and 0.9% physiological saline were sterilized at 120°C for 15 min. Melted agar aliquots (15 mL each) were aseptically transferred to petri dishes and allowed to solidify completely at room temperature. Before the antibacterial test, the membrane samples (0.5 cm in diameter) were sterilized by UV irradiation in a laminar flow hood, with each side irradiated for 30 min. For the assay, 1 mL of bacterial suspension (10... 7 ~10 8 CFU / mL culture medium was added to 14 mL of physiological saline containing the sample and incubated at 37°C with shaking for 24 h. Subsequently, 20 μL of culture medium was spread onto agar plates using a sterile disposable spreader, and incubated at 37°C for another 24 h. The number of surviving colonies was then counted. Three replicates were prepared for each sample group, with Comparative Example 1 serving as a blank control. Results are expressed as mean ± standard deviation (SD). The inhibition rate was calculated using the following formula:
[0071]
[0072] Where A represents the number of colony-forming units (CFU) in CCF, and B represents the number of CFU in the example and control groups.
[0073] (7) Tensile strength
[0074] The tensile properties of the composite film were tested using a UTM2203 universal testing machine according to GB / T 1040.3 standard. The film was cut into 6 cm × 1 cm pieces and stretched at 100 mm / min under a standard environment of (23±2)℃ and 50% relative humidity until the sample broke. The maximum tensile load was recorded and the tensile strength was calculated.
[0075] The raw materials and their sources involved in the embodiments and comparative examples of this invention are as follows:
[0076] The wood pulp filter paper was purchased from Hangzhou Fuyang Beizhi Paper Co., Ltd.
[0077] Gardenia Yellow ( = 21.2 (purity 95%) was purchased from Henan Zhongda Hengyuan Biotechnology Co., Ltd.
[0078] Chitosan (degree of deacetylation ≥ 95%, Mw = 250 kDa) was purchased from Aladdin Biochemical Technology Co., Ltd.
[0079] The microbial strains (Escherichia coli ATCC25922 and Staphylococcus aureus ATCC29213) were purchased from Aladdin Biochemical Technology Co., Ltd.
[0080] In the embodiments and comparative examples of this invention:
[0081] The preparation method of carboxymethyl cellulose powder includes the following steps: Wood pulp filter paper is pulverized using a mechanical pulverization process, then ground into powder using a grinder. 30 g of cellulose powder is weighed and dissolved in 1000 mL of 1M sodium chloroacetate and 15% sodium hydroxide solution, and stirred continuously at 50°C for 2 h to carry out an etherification reaction. After the reaction is complete, the mixture is washed with deionized water until neutral and dried in an oven at 65°C for 4 h. Subsequently, the cellulose fibers are ground to 60-80 mesh to obtain carboxymethyl cellulose powder.
[0082] A method for preparing phosphorylated chitosan (PCS) powder includes the following steps: 20 g of chitosan, 30 mL of acetic acid, 200 mL of phosphoric acid, and 300 mL of distilled water are added to a reaction vessel and stirred at 50°C for 4 hours. The resulting liquid is then slowly added dropwise to ethanol, forming a white solid precipitate. The precipitate is collected, filtered, and washed repeatedly with ethanol to remove residual acidic reactants. Finally, the sample is dried and ground to obtain phosphorylated chitosan (PCS) powder. The calculated degree of phosphate substitution (DSp) of PCS is 0.93%.
[0083] Example 1
[0084] A method for preparing a composite thin film includes the following steps:
[0085] (1) 5 g of carboxymethyl cellulose powder was dissolved in 200 g of an aqueous solution containing lithium hydroxide and urea. The lithium hydroxide-urea aqueous solution had a mass fraction of 8% and a mass fraction of urea of 15%. The solution was continuously stirred until homogeneous. After sealing, the solution was frozen at -18°C for 12 h and then thawed at room temperature to obtain a transparent cellulose aqueous solution. The prepared cellulose aqueous solution was poured into a 150 cm × 20 cm × 3 cm mold and allowed to stand. Then, 250 mL of ethanol was poured in and the solution was cured at room temperature for 6 h. The alkalinity in the hydrogel was removed by soaking in deionized water to obtain a transparent carboxymethyl cellulose hydrogel with a thickness of about 1.2 mm.
[0086] (2) Take 0.4 g of gardenia yellow powder and 1.5 g of phosphorylated chitosan powder and add them to 100 g of deionized water. Use a high-speed homogenizer to disperse them at a speed of 10000 r / min for 15 min to obtain a uniform composite solution.
[0087] (3) After cutting the carboxymethyl cellulose hydrogel (e.g., 8 cm × 8 cm), immerse it in the composite solution and let it stand at 25°C in the dark for 2 h to promote the penetration and fixation of the functional components in the matrix.
[0088] (4) Remove the hydrogel block and fix it with a metal clip to prevent shrinkage, then dry it in air at 25°C. The moisture content is controlled below 5% to obtain a homogeneous and flat composite film, named GPCS-CCF1, with a thickness of about 0.12 mm.
[0089] Example 2
[0090] The difference from Example 1 is that in Example 2, 0.6g of gardenia yellow was used, and the rest was the same as in Example 1. The prepared composite film was named GPCS-CCF2.
[0091] Example 3
[0092] The difference from Example 1 is that in Example 3, 0.8g of gardenia yellow was used, and the rest was the same as in Example 1. The prepared composite film was named GPCS-CCF3.
[0093] Comparative Example 1
[0094] Comparative Example 1 uses a pure carboxymethyl cellulose film as a blank control. Specifically, Comparative Example 1 involves cutting the transparent carboxymethyl cellulose hydrogel prepared in step (1) of Example 1 (e.g., 8 cm × 8 cm in size), fixing it with metal clips to prevent shrinkage, and then drying it in air at 25°C. The moisture content is controlled below 5%, resulting in a pure carboxymethyl cellulose film, named CCF.
[0095] Comparative Example 2
[0096] The difference from Example 1 is that step (2) of Comparative Example 2 is as follows: 0.8 g of Gardenia Yellow Powder (GY) is added to 100 g of deionized water and dispersed at high speed for 15 min using a high-speed homogenizer at a speed of 10000 r / min to obtain a uniform composite solution. The rest is the same as in Example 1.
[0097] Comparative Example 3
[0098] The difference from Example 1 is that step (2) of Comparative Example 3 is as follows: 1.5 g of phosphorylated chitosan powder (PCS) is added to 100 g of deionized water and dispersed at high speed for 15 min using a high-speed homogenizer at a speed of 10000 r / min to obtain a uniform composite solution. The rest is the same as in Example 1.
[0099] Comparative Example 4
[0100] The difference from Example 1 is that step (2) of Comparative Example 4 is as follows: 1.5g of chitosan powder is added to 100mL of acetic acid solution with a mass fraction of 2% to obtain a composite solution. The rest is the same as in Example 1.
[0101] Comparative Example 5
[0102] The difference from Example 1 is that an equal mass of chitosan powder is used instead of phosphorylated chitosan powder. Everything else is the same as in Example 1.
[0103] Comparative Example 6
[0104] The difference from Example 1 is that the amount of phosphorylated chitosan powder added in Comparative Example 6 is 5g, while the rest is the same as in Example 1.
[0105] Comparative Example 7
[0106] The difference from Example 1 is that the amount of Gardenia Yellow added in Comparative Example 7 is 0.2g, while the rest is the same as in Example 1.
[0107] Comparative Example 8
[0108] The difference from Example 1 is that the amount of Gardenia Yellow added in Comparative Example 8 is 2g, while the rest is the same as in Example 1.
[0109] Experimental results:
[0110] (1) Characterization of GPCS-CCFs
[0111] Figure 1 Figure (a) shows the synthetic route of PCS. In this process, phosphoric acid acts as a phosphorylating agent, with its phosphorus atom acting as an electron-deficient center. This phosphorus atom is nucleophilically attacked by the lone pair of electrons from the hydroxyl group (-OH) in the CS molecule, resulting in a nucleophilic substitution reaction and ultimately forming a phosphate ester bond. The FTIR spectra of CS and PCS are shown below. Figure 1 As shown in (b), CS is at 1660 cm. -1 An amino absorption peak is present at 1592 cm⁻¹. -1 The vibration at this point is caused by the bending vibration of NH. And at 1160 cm... -1 and 1032 cm -1 The absorption peaks at 950 cm⁻¹ are attributed to the CO stretching vibration in -CH-OH and the stretching vibration of asymmetric COC, respectively. PCS at 950 cm⁻¹ -1 The P-OH stretching vibration peak at 1535 cm⁻¹ indicates that CS has undergone phosphorylation. Meanwhile, at 1535 cm⁻¹... -1 The new peak generated at 1592 cm⁻¹ is due to the PCS at 1592 cm⁻¹. -1 The red shift indicates that the hydrogen atom in the amino group has been replaced by a phosphate group, thus forming an NP bond. Furthermore, at 1637 cm⁻¹... -1 The NH peak at [location] indicates that some amino groups participated in the reaction. The Fourier transform infrared (FTIR) spectra of cellulose fibers and carboxymethylated cellulose fibers are shown below. Figure 1 As shown in (c). Carboxymethylated cellulose fibers at 1590 cm⁻¹ -1 The presence of a strong absorption peak due to asymmetric stretching vibrations indicates the presence of COO. - The expansion joint confirmed the success of cellulose carboxymethylation. For example... Figure 1 As shown in (d), GY exhibits its characteristic hydroxyl groups (3372 cm). -1 ), alkyl (2919 cm) -1 ) and CO (1372 cm -1 ) and COC (1063 cm -1 The stretching vibration peaks were observed. Compared to CCF, the positions of the main skeletal peaks did not show significant chemical shifts, indicating that the introduction of GY and PCS mainly binds to the cellulose matrix through non-covalent interactions, maintaining the inherent structure of cellulose. GPCS-CCFs showed a peak at 3265 cm⁻¹. -1The OH stretching peak at the point of origin shows a significant increase in width and a decrease in intensity compared to CCF. This typical feature clearly indicates a significant enhancement of hydrogen bonding in the composite system, forming a complex multi-layered hydrogen bond network among cellulose, carboxyl, phosphate, amino, and hydroxyl groups. These strong intermolecular interactions are the key driving force for promoting the tight bonding of the components and endowing the composite film with excellent synergistic properties.
[0112] To investigate the crystal structure of each component and the phase changes of the complex, X-ray diffraction (XRD) analysis was performed on PCS, GY, CCF, and GPCS-CCFs. The results are as follows: Figure 1 As shown in (e), the diffraction pattern of CCF exhibits three clear diffraction peaks at 2θ = 12.4°, 20.8°, and 22.2°, which are consistent with the characteristic diffraction peaks of the (1-10), (110), and (020) crystal planes of cellulose type II crystals, indicating that it has a typical cellulose II crystal structure. In contrast, the XRD pattern of GY shows only a very broad diffuse peak at about 18°, accompanied by an amorphous background from low angle to 50°, revealing that it is essentially a low-crystallinity or amorphous state. The XPS spectra of CCF and GPCS-CCFs are shown in (e). Figure 1 As shown in (f). CCF contains only carbon and oxygen, and its characteristic peaks for O1s and C1s are located at 532 eV and 286 eV, respectively. Figure 1 In the middle (g) sample, a new characteristic peak appeared at 132 eV in GPCS-CCF3, indicating the presence of phosphorus. XPS results confirmed that PCS had been successfully introduced into the composite membrane matrix.
[0113] like Figure 1 Image (h) shows the cross-sectional SEM images of CCF and GPCS-CCFs. It can be seen that the cross-section of CCF is relatively flat, smooth, and has a dense structure. The cross-sectional morphology of GPCS-CCFs is almost identical, indicating that the addition of PCS and GY has almost no effect on the cross-sectional area of the material. Furthermore, it is evident that PCS and GY are uniformly distributed in cellulose; even at the highest GY concentration, no particle adhesion or aggregation was observed in the cross-section of GPCS-CCF3.
[0114] (2) UV and blue light shielding performance of GPCS-CCFs
[0115] Figure 2 Image (a) shows photographs of CCF and GPCS-CCFs against a background of "Cellulose". The background text is clearly visible, indicating that all samples possess good transparency. As the concentration of gardenia yellow increases, the color of the membrane gradually deepens, but its transparency remains unaffected. The UV-Vis transmittance curves of CCF and GPCS-CCFs are shown below. Figure 2 As shown in (b), CCF exhibits high visible light transmittance, reaching 90% at 600 nm. However, its shielding ability against blue and ultraviolet light is weak, with shielding rates of 16.9%, 13%, and 10.8% against UV-B, UV-A, and high-energy blue light, respectively. Figure 2 (e)). In contrast, GPCS-CCFs significantly improve UV and blue light shielding performance while maintaining high transmittance. Figure 2 (c) and (d)). GPCS-CCF1 has a transmittance of 90.8% at 600 nm, and its shielding rates against UV-B, UV-A, and HEBL are improved to 55.6%, 52.5%, and 72.5%, respectively. GPCS-CCF2 further improves its shielding rates against these three UV-B, UV-A, and HEBL to 64.3%, 64.3%, and 86.7%, respectively. GPCS-CCF3 achieves shielding rates of 68.3%, 69.9%, and 91.1%, respectively. Figure 2 (e)). To visually verify the ultraviolet shielding performance of the material, the experiment used an ultraviolet lamp to irradiate an ultraviolet sensing card covered by the sample. The results are as follows: Figure 2 As shown in (f), the color of the CCF-covered area remained almost unchanged after ultraviolet light irradiation, indicating that it does not have effective ultraviolet shielding capability. In contrast, the GPCS-CCFs-covered area showed virtually no color change, confirming that it has a significant ultraviolet shielding effect.
[0116] A systematic evaluation of the haze of CCF and GPCS-CCFs was conducted. In practical applications such as display devices, transparent glass windows, automotive windshields, and optoelectronic functional materials, GPCS-CCFs, with their lowest haze and excellent light transmittance, are highly favored. The haze levels of CCF and GPCS-CCFs are as follows: Figure 3 As shown. (Through) Figure 3 It can be seen that the haze of GPCS-CCFs did not change with the increase of GY content, indicating that the addition of GY and PCS had no effect on the optical properties of the film.
[0117] (3) Flame retardant properties of GPCS-CCFs
[0118] This application tested the thermal stability and limiting oxygen index (LOI) of CCF and GPCS-CCFs. Figure 4Tables (a) and (b) show the TGA and DTG curves of CCF and GPCS-CCFs. Within the temperature range of 100–600 °C, the mass of all films gradually decreased with increasing temperature. A slight mass loss was observed in the range of 100 °C to 220 °C, due to the evaporation of adsorbed water. For CCF, a significant and sharp mass loss occurred in the range of 220 °C to 350 °C, accounting for 52% of the total weight loss, caused by the thermal decomposition of cellulose. The final stage of weight loss occurred between 350 and 600 °C, corresponding to the decomposition of carbonaceous matter. Compared with CCF, GPCS-CCFs showed a significantly slower rate of mass loss between 220 °C and 270 °C. The decomposition of the carbonaceous component in GPCS-CCFs began at 270 °C. At 600 °C, the residual mass ratio of GPCS-CCFs reached 36%, significantly higher than that of CCF. This result confirms that GPCS-CCFs possess superior thermal stability. Figure 4 As shown in (c), the LOI value of CCF is only 19.2%, reflecting its highly flammable characteristics. Notably, the introduction of PCS and GY networks significantly increases this value to 31.1%, 31.3%, and 32.1% for the corresponding GPCS-CCFs.
[0119] (4) Water contact angle of GPCS-CCFs and barrier properties against water vapor and gas
[0120] This application also conducted a water contact angle (WCA) test to evaluate the hydrophobic / hydrophilic properties of the prepared film, and the results are as follows: Figure 5 As shown in the figure, the water contact angle of the control CCF was 48.6°. After modification with GY and PCS, the water contact angle of GPCS-CCFs showed a significant increasing trend. The water contact angles of GPCS-CCF1, GPCS-CCF2, and GPCS-CCF3 were 50.5°, 54.4°, and 61.4°, respectively. It can be seen that introducing GY and PCS into the cellulose matrix enhances the surface hydrophobicity of GPCS-CCFs. In addition, to further evaluate the application potential of the film in the packaging field, this application systematically measured the water vapor permeability and oxygen and carbon dioxide barrier properties of CCF and GPCS-CCF. Figure 6 As shown in (a), the water vapor transmission rate of the CCF is 8.84 × 10⁻⁶. -11 g·m -1 ·s -1 ·Pa -1 GPCS-CCFs decreased to 8.42 × 10⁻⁶. -11 g·m -1 ·s -1 ·Pa -1 7.90 ×10 -11 g·m -1·s -1 ·Pa -1 and 7.61 × 10 -11 g·m -1 ·s -1 ·Pa -1 The oxygen permeability of the CCF is 3.84 cm. 3 / m 2 •24h•0.1Mpa, while GPCS-CCFs were 3.65 cm 3 / m 2 24h 0.1Mpa, 3.37 cm 3 / m 2 ·24h·0.1Mpa and 3.01 cm 3 / m 2 • 24h • 0.1MPa. The carbon dioxide transmission rate of the CCF is 1.42 cm³ / m. 2 ·24h·0.1Mpa, while GPCS-CCFs decreased to 1.31 cm 3 / m 2 ·24h·0.1Mpa, 1.23 cm 3 / m 2 ·24h·0.1Mpa and 1.10 cm 3 / m 2 • 24h • 0.1 MPa. The above results indicate that the introduction of GY and PCS gradually improves the barrier properties of the film against water vapor and gases. This comprehensive improvement in barrier properties, combined with enhanced surface hydrophobicity, suggests that GPCS-CCFs have great potential as packaging materials.
[0121] (5) Antibacterial properties of GPCS-CCFs
[0122] This application also tested the antibacterial properties of GPCS-CCFs, and the results are as follows: Figure 7 As shown, through Figure 7 It can be seen that CCF has almost no antibacterial activity, and the surface of the culture medium is covered with dense colonies. In contrast, GPCS-CCFs containing GY and PCS exhibit good bacterial inhibition effects. Specifically, GPCS-CCF1, GPCS-CCF2, and GPCS-CCF3 showed inhibition rates of 70.7%, 74.8%, and 82.5% against Escherichia coli, respectively, while their inhibition efficiencies against Staphylococcus aureus were 70%, 71.4%, and 75.5%, respectively. The antibacterial properties of GPCS-CCFs stem from the synergistic effect of GY and PCS. PCS, with its cationic group (-NH3), provides the antibacterial effect. +The GPCS-CCFs electrostatically adsorb onto the negatively charged bacterial cell membrane, capturing bacteria and initially disrupting the membrane structure. GY, a natural polyphenol, inserts into the hydrophobic core region of the membrane after PCS adsorption, deeply disrupting membrane integrity through oxidative stress and lipid peroxidation, triggering irreversible leakage of intracellular substances. This creates a synergistic "capture-membrane disruption" cascade effect. This composite film operates on a contact sterilization mode, with active ingredients released independently of dissolution. Due to the limited total amount of GY and PCS loaded in the hydrogel, primarily distributed on the membrane surface or in the pores, an effective concentration gradient is difficult to form in agar medium, thus no inhibition zone is generated. GPCS-CCFs show slightly better inhibitory effects against *Escherichia coli* than *Staphylococcus aureus*, attributed to differences in their cell wall structures. The outer membranes of negative-negative bacteria are rich in lipopolysaccharides, making them more susceptible to adsorption by PCS cationic groups and polyphenol destruction. Conversely, the thicker, dense peptidoglycan layer of positive-negative bacteria creates significant spatial barriers to physical contact and polyphenol penetration, further confirming the material's bactericidal nature, which is primarily based on contact-dependent physical membrane disruption. In summary, this antimicrobial mechanism, with 'contact sterilization' as its core, ensures the efficient retention and long-lasting protection of active ingredients on the material surface. This allows it to provide strong antifouling and hygienic protection for electronic product interfaces while ensuring food contact safety, thus meeting the stringent requirements for microbial control on material surfaces in various complex usage scenarios.
[0123] (6) Mechanical properties of GPCS-CCFs
[0124] Mechanical properties are one of the core indicators for evaluating the practical value and application adaptability of functional cellulose films. Figure 8 Figures (a) and (b) demonstrate the tensile mechanical properties of CCF and GPCS-CCFs. As a control sample, pure CCF exhibits an average maximum tensile strength of 72.2 MPa. As expected, the addition of GY and PCS affects the mechanical properties of GPCS-CCFs. Compared to CCF, GPCS-CCFs demonstrate enhanced tensile strength, with GPCS-CCF1, GPCS-CCF2, and GPCS-CCF3 exhibiting tensile strengths of 80.2 MPa, 84.1 MPa, and 85.7 MPa, respectively. Furthermore, Figure 8 Image (c) clearly demonstrates the excellent flexibility of GPCS-CCFs. After repeated deformation operations such as bending, folding, and twisting, the film maintains its intact structure without any cracks or damage, fully verifying its excellent deformation adaptability. This characteristic enables the film to be applied to special scenarios such as curved screen bonding and foldable packaging protection, effectively broadening the application range of the material and further enhancing its practical value.
[0125] The comprehensive performance comparison of the films prepared in Examples 1-3 and Comparative Examples 1-8 of this invention is detailed in Table 1.
[0126] Table 1. Overall performance of the films prepared in Examples 1-3 and Comparative Examples 1-8
[0127]
[0128] In summary, based on Table 1 and Figures 1-8 As can be seen from Examples 1-3, the composite films prepared by this invention possess high transparency, low haze, flame retardancy, antibacterial activity, and broad-spectrum harmful light shielding capability from ultraviolet to blue light. A key feature of these films is their highly efficient high-energy blue light (HEBL) filtering performance, with a blocking rate as high as 72.5% to 91.1%. Furthermore, they exhibit significant ultraviolet protection capabilities, with UV-A protection efficiency of 52.5%–69.9% and UV-B protection efficiency of 55.6%–68.3%. Moreover, these excellent optical management capabilities do not come at the expense of transparency and haze. At a wavelength of 600 nm, the transmittance of these films remains between 90% and 90.8%, and the haze level is between 1.8% and 2.0%. Therefore, the composite films prepared by this invention can effectively protect against blue light radiated from lighting systems, smartphone screens, and computer screens. Furthermore, the composite films prepared by this invention exhibit excellent fire resistance, with the limiting oxygen index (LOI) significantly improved from 19.2% to over 30%. These films exhibit excellent mechanical properties, and also possess antibacterial activity. This research provides an all-biomass material solution for high-performance optoelectronic device packaging, flexible smart protection, and food packaging.
[0129] A comparison of Example 3 with Comparative Examples 2 and 3 shows that Comparative Example 2 uses only Gardenia Yellow as a functional component. Although its light shielding ability is stronger than that of Example 3, its flame retardancy and antibacterial properties are poor. Comparative Example 3 uses only Phosphorylated Chitosan as a functional component. Although its flame retardancy is stronger than that of Example 3, its light shielding performance is far lower than that of Example 3, and its antibacterial rate is also poor. It can be seen that the functional components Gardenia Yellow and Phosphorylated Chitosan are indispensable. The two work together to give the film excellent comprehensive performance.
[0130] A comparison of Example 3 with Comparative Examples 3, 4, and 5 shows that phosphorylated chitosan exhibits significant advantages in flame retardancy and antibacterial properties compared to ordinary chitosan. It not only effectively improves the flame retardant properties of the film but also enhances its antibacterial properties.
[0131] The comparison between Example 3 and Comparative Example 6 shows that the amount of phosphorylated chitosan added needs to be controlled within a reasonable threshold. When the amount added exceeds the appropriate range, not only will the optical properties of the film decrease, but the flame retardant and antibacterial properties of the film will also weaken.
[0132] The comparison between Example 3 and Comparative Examples 7 and 8 shows that the amount of gardenia yellow added also needs to be within a reasonable range. When the amount of gardenia yellow added is too small, the chromophore concentration is insufficient, resulting in weakened optical properties of the film and an inability to fully interact with phosphorylated chitosan. When the amount of gardenia yellow added is too large, it easily disrupts the uniformity of the film, leading to a decrease in the film's optical shielding efficiency, and simultaneously weakening other properties.
[0133] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.
Claims
1. A method for preparing a multifunctional composite film that shields harmful light, is flame-retardant, and antibacterial, characterized in that, Includes the following steps: S1. Dissolve carboxymethyl cellulose powder in an aqueous solution of lithium hydroxide-urea, disperse it thoroughly, freeze it, thaw it at room temperature, place it in a mold, add ethanol to solidify it, and obtain a transparent cellulose hydrogel. S2. Gardenia yellow and phosphorylated chitosan were added to deionized water and dispersed at high speed to obtain a composite solution. S3. After cutting the cellulose hydrogel obtained in step S1 into pieces, immerse it completely in the composite solution obtained in step S2 and soak it thoroughly so that the functional components can fully penetrate into the three-dimensional network of the hydrogel. S4. The soaked film is dried to prepare the composite film.
2. The method for preparing the composite thin film according to claim 1, characterized in that, In step S1, the carboxymethyl cellulose powder is obtained by adding cellulose powder to an aqueous solution containing sodium chloroacetate and sodium hydroxide to carry out a carboxymethylation reaction. After the reaction is completed, the powder is washed with deionized water until neutral, dried, and ground to obtain carboxymethyl cellulose powder. Further, the cellulose powder is one or more of cotton pulp cellulose powder, wood pulp cellulose powder, or straw cellulose powder, the mass concentration of sodium hydroxide is 10% to 20%, the concentration of sodium chloroacetate is 0.5 to 1.5 M, the solid-liquid ratio of cellulose powder to an aqueous solution containing sodium chloroacetate and sodium hydroxide is 1:30 to 1:40 g / mL, the carboxymethylation reaction temperature is 50℃ to 70℃, and the reaction time is 2 h to 5 h.
3. The method for preparing the composite thin film according to claim 1, characterized in that, In step S1, the lithium hydroxide-urea aqueous solution contains lithium hydroxide at a mass fraction of 5% to 10% and urea at a mass fraction of 10% to 20%. The freezing temperature is -50℃ to -10℃ and the freezing time is 2 h to 12 h. The curing temperature is 10℃ to 25℃ and the curing time is 4 h to 12 h.
4. The method for preparing the composite thin film according to claim 1, characterized in that, In step S2, the mass ratio of gardenia yellow, phosphorylated chitosan, and deionized water in the composite solution is 0.4-1.0g: 1-2g: 100g; more preferably 0.6-0.8g: 1.2-1.8g: 100g; even more preferably 0.8g: 1.5g: 100g.
5. The method for preparing the composite thin film according to claim 1, characterized in that, The phosphorylated chitosan is prepared by adding chitosan to an aqueous solution of acetic acid and phosphoric acid, stirring and reacting at 40-60°C for 3-5 hours, then pouring it into anhydrous ethanol to precipitate a white precipitate, and then washing, drying and pulverizing it to obtain phosphorylated chitosan powder.
6. The method for preparing the composite thin film according to claim 5, characterized in that, In an aqueous solution of acetic acid and phosphoric acid, the volume concentration of acetic acid is 4-8%, and the volume concentration of phosphoric acid is 35-40%. And / or, the ratio of chitosan to phosphoric acid is 1 g: (9-12) mL.
7. The method for preparing the composite thin film according to claim 1, characterized in that, In step S2, the high-speed dispersion is carried out at a rotation speed of 8000-12000 r / min for 10-20 min; And / or, in step S3, the soaking is carried out at room temperature and in the dark for 2 to 4 hours.
8. A multifunctional composite film that shields harmful light, is flame-retardant, and antibacterial, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 7.
9. The composite film according to claim 8, characterized in that, The composite film has a thickness of 0.10~0.15mm; a shielding efficiency of ≥52.5% at 320~400 nm, a shielding efficiency of ≥55.6% at 280~320 nm, a shielding efficiency of ≥72.5% at 400~450 nm, a limiting oxygen index of ≥31.1%, an antibacterial rate of ≥70% against Escherichia coli, an antibacterial rate of ≥70% against Staphylococcus aureus, and a tensile strength of ≥80 MPa. Furthermore, the composite film maintains a high transmittance of over 90% and a low haze of 1.8–2.0% at a wavelength of 600 nm.
10. The application of a composite film in flexible optoelectronic devices and packaging materials, characterized in that, The composite film is the composite film prepared by the method according to any one of claims 1 to 7, or the composite film according to any one of claims 8 or 9; Furthermore, the composite film is used to prepare screen protectors for electronic devices or protective liner for photosensitive foods.